2008
DOI: 10.1002/er.1364
|View full text |Cite
|
Sign up to set email alerts
|

A cost-effective operating strategy to reduce energy consumption in a HVAC system

Abstract: SUMMARYThe operation of the building heating, ventilating, and air conditioning (HVAC) system is a critical activity in terms of optimizing the building's energy consumption, ensuring the occupants' comfort, and preserving air quality. The performance of HVAC systems can be improved through optimized supervisory control strategies. Set points can be adjusted by the optimized supervisor to improve the operating efficiency. This paper presents a cost-effective building operating strategy to reduce energy costs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…Therefore, minimizing the objective function (14) can push y 2 (t) and y 3 (t) towards their bounds. Then, the optimization model can be modified to (15 subject to :…”
Section: Optimization Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, minimizing the objective function (14) can push y 2 (t) and y 3 (t) towards their bounds. Then, the optimization model can be modified to (15 subject to :…”
Section: Optimization Modelmentioning
confidence: 99%
“…5 demonstrates the fitness function values for different ratios of parent and offspring sizes. Note that the objective function at the vertical axis refers to the obj 1 in model (15), not the fitness values computed in Eqs. (16) and (17) at each generation.…”
Section: Usually In Step 3 Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective function J operational represents the total energy consumption of the system during the optimization period due to the chiller supplying chilled water to both the DV cooling coil unit and the CC panel, fans, reheat, and water circuit pump. The optimization solver of Mossolly et al [1,31] will be used based on a genetic algorithm solver [32][33][34][35][36] that is able to identify the pay-off characteristics between daily energy cost and zone thermal discomfort and IAQ. The operation of the DV and CC system for each of the nine selected designs of subsystem combinations meeting the load will be optimized in response to the space load using a control strategy where both CC temperature and supply air conditions of temperature and flow rate can be simultaneously varied [1].…”
Section: Optimizationmentioning
confidence: 99%
“…Experimental results were shown that the residual ratio can be used to diagnose and accurately identify and detect multiple faults occurring in HVAC systems. Nassif and Moujaes [2] present a cost-effective building operating strategy to reduce energy costs associated with the operation of the HVAC system. The proposed strategy could reduce energy consumption by about 11% when compared with the actual strategy applied on the investigated existing system.…”
Section: Introductionmentioning
confidence: 99%